Phylogenetic study of endophytic fungi associated with Centella asiatica from Bengkulu and Malaysian accessions based on the ITS rDNA sequence - NANI RADIASTUTI; DWI NINGSIH SUSILOWATI; HUSHSHILA A BAHALWAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Radiastuti N, Bahalwan HA, Susilowati DN. 2019. Phylogenetic study of endophytic fungi associated with Centella asiatica from Bengkulu and Malaysian accessions based on the ITS rDNA sequence. Biodiversitas 20:  1248-1258. Centella asiatica is one of the medicinal plants which is known to be symbiotic with various endophytic fungi. The purpose of this research was to determine diversity of culturable fungal endophyte from C. asiatica. Identification was conducted using molecular phylogenetic analysis based on the ITS rDNA sequence. The result showed that obtained 145 isolates endophytic fungi (from stolons, leaves, roots, petioles) were grouped into 18 morphotaxa (Bengkulu) and 23 morphotaxa (Malaysian). The fungal endophytic were identified as Aspergillus austroafricanus, Aspergillus oryzae, Acrocalymma vagum, Ceratobasidium cornigerum, Ceratobasidium sp., Chaetomium globosum, Colletotrichum karstii, C. gigasporium, C. tabaci, Colletotrichum siamense, Eutypella sp., Fusarium solani, F. oxysporum, F. falciforme, F. keratoplasticum, F. striatum, Fusarium sp., Penicillium capsulatum, Phoma multirostrata, Perenniporia tephropora, Perenniporia sp., Phanerochaete chrysosporium, Phanerochaete stereoides, Phyllosticta capitalensis, Phomopsis asparagi, Peroneutypa scoparia, Phialemoniopsis sp., Mycochaetophora gentinae, Talaromyces sp., Earliella scabrosa, and Trichaptum sp. based on molecular phylogenetic analysis. Fusarium (Nectriaceae) were the most found of fungal endophytes in both C. asiatica Bengkulu and Malaysian accession. The majority strain are including Ascomycetes and Basidiomycetes. The identification of endophytic fungi from medicinal plants is needed as a preliminary study to determine the potential of endophytic fungi producing bioactive compounds.